Leadership practices of physical education teachers and student-related outcomes: a systematic mixed method review and analysis - Kim, Hyun-Duck; Cruz, Angelita Bautista (Frontiers in Psychology, 2024)
This study systematically reviewed and analyzed both qualitative and quantitative studies that focused on the relationship between physical education (PE) teachers' leadership and student outcomes using data mining and meta-analysis. Findings from the data-mining analysis using Leximancer revealed eight major themes associated with PE teacher leadership, emphasizing motivation, education, support, and teaching. Results from the meta-analysis using the Comprehensive Meta-Analysis software showed that autonomy-supporting behaviors showed strong positive effects on student satisfaction, motivation, competence, and engagement. Regional differences in research focus were observed, with health being less emphasized in Asian and European studies. Student sex emerged as a moderating factor. The study highlights the role of PE teacher leadership and the convergence/divergence among research findings.